(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Salinity is a devastating abiotic stress worldwide; seriously hamper crop production through altering growth and biochemical constituents of plants at the coastal ecosystem. Growing salt tolerant genotypes is the most effective strategy to improve crop production in the ecosystem. Objective of the experiment was to investigate the saline induced changes in growth and biochemical constituents of different chili genotypes, and identify salt tolerant chili genotype. The study evaluated three chili genotypes—Anal 1701, Black Kobra, and Traditional variety—grown under varying salinity levels (0, 3, 6, 9, and 12 dSm-1 at the germination stage; and 0, 3, and 6 dSm-1 at the vegetative stage) using a two-factorial completely randomized design with three replications during Rabi season of 2024. Salinity stress had a significant impact on plant height, proline, and chlorophyll content during the vegetative stage (P < 0.001). Anal 1701 showed the greatest proline concentration (38.54 mg 100 g⁻¹ fresh leaf) and chlorophyll-a content (4.75 mg g-1 fresh leaf). Traditional variety and Black Kobra came in second and third, respectively; while Black Kobra showed lowest chlorophyll-a concentration (1.05 mg g-1 fresh leaf). During germination stage up to 6 dSm-1 salinity level the root and shoot growth was increased; thereafter increasing salt concentration drastically reduced the parameters. The germination and vegetative stage experiment suggested that the Anal 1701 chili cultivar be cultivated in the soils influenced by coastal salt with an alternative of traditional variety. The study’s conclusions will help to choose chili genotypes for upcoming breeding initiatives that try to increase salinity tolerance and reduce production loss. J Bangladesh Agril Univ 23(1): 33–41, 2025